ANALISIS DAMPAK LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA ( Studi Kasus Pada Badan Kepegawaian Daerah Kabupaten Kutai Timur ) - Hasanah, Siti (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the work environment has a positive influence on Employee Job Satisfaction At the Regional Employment Board of East Kutai.The results showed that there is a positive and significant relationship between the variables of the Work Environment variables Employee Job Satisfaction At the Regional Employment Board of East Kutai. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.613, which means there is a strong and positive relationship between the two variables.While the results of the t test (t-test) demonstrated that the resulting empirical t is equal to 5.260. These results are more bear comparison with the prices of the table critical t for n - 2 is 1.691. This means that there is a significant influence between the variables of Work Environment on Employee Job Satisfaction. Thus it can be said that the goal of this research can be achieved, the problems can be solved and the hypothesis can be proven.Â